The Informative Process Model as a New Intervention for Attitude Change in Intractable Conflicts: Theory and Empirical Evidence - Rosler, Nimrod; Sharvit, Keren; Hameiri, Boaz; Wiener-Blotner, Ori; Idan, Orly; Bar-Tal, Daniel (Frontiers in Psychology, 2022)
Peacemaking is especially challenging in situations of intractable conflict. Collective narratives in this context contribute to coping with challenges societies face, but also fuel conflict continuation. We introduce the Informative Process Model (IPM), proposing that informing individuals about the socio-psychological processes through which conflict-supporting narratives develop, and suggesting that they can change via comparison to similar conflicts resolved peacefully, can facilitate unfreezing and change in attitudes. Study 1 established associations between awareness of conflict costs and conflict-supporting narratives, belief in the possibility of resolving the conflict peacefully and support for pursuing peace among Israeli-Jews and Palestinians. Studies 2 and 3 found that exposure to IPM-based original videos (vs. control) led Israeli-Jews to deliberation of the information presented, predicting acceptance of the IPM-based message, which, in turn, predicted support for negotiations. Study 3 also found similar effects across IPM-based messages focusing on different conflict-supporting themes. We discuss the implications to attitude change in intractable conflicts.